2013
DOI: 10.1073/pnas.1215844110
|View full text |Cite
|
Sign up to set email alerts
|

Emergent relation between surface vapor conductance and relative humidity profiles yields evaporation rates from weather data

Abstract: The ability to predict terrestrial evapotranspiration (E) is limited by the complexity of rate-limiting pathways as water moves through the soil, vegetation (roots, xylem, stomata), canopy air space, and the atmospheric boundary layer. The impossibility of specifying the numerous parameters required to model this process in full spatial detail has necessitated spatially upscaled models that depend on effective parameters such as the surface vapor conductance (C surf ). C surf accounts for the biophysical and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(121 citation statements)
references
References 17 publications
5
91
0
Order By: Relevance
“…A complete description of the stability functions for m and v is presented in Supplement 2. Further, the roughness height for water vapor (z 0v ) is estimated using the so-called kB −1 approach (Crago and Suleiman, 2005;Crago et al, 2010) relating the momentum (z 0m ) and scalar (z 0v ) roughness heights to the roughness Reynolds number R e * as follows (Salvucci and Gentine, 2013):…”
Section: Model Descriptionsmentioning
confidence: 99%
“…A complete description of the stability functions for m and v is presented in Supplement 2. Further, the roughness height for water vapor (z 0v ) is estimated using the so-called kB −1 approach (Crago and Suleiman, 2005;Crago et al, 2010) relating the momentum (z 0m ) and scalar (z 0v ) roughness heights to the roughness Reynolds number R e * as follows (Salvucci and Gentine, 2013):…”
Section: Model Descriptionsmentioning
confidence: 99%
“…Specifically, Salvucci and Gentine (2013) found that the surface conductance to water vapor transport, the key rate-limiting parameter of typical evapotranspiration models, can be estimated as the value that minimizes the vertical variance of the calculated relative humidity profile averaged over the day. The key advantage of this approach is that biophysical and hydrological surface parameters (stomatal conductance, soil texture, soil moisture, etc.)…”
Section: Etrheq-based Evapotranspiration Productmentioning
confidence: 99%
“…The Rigden and Salvucci (2015) evapotranspiration dataset was derived from meteorological data using a method based on the relationship between the diurnal cycle of relative humidity and evapotranspiration (Salvucci and Gentine, 2013)-a method known as "ETRHEQ" (evapotranspiration based on relative humidity at equilibrium). Specifically, Salvucci and Gentine (2013) found that the surface conductance to water vapor transport, the key rate-limiting parameter of typical evapotranspiration models, can be estimated as the value that minimizes the vertical variance of the calculated relative humidity profile averaged over the day.…”
Section: Etrheq-based Evapotranspiration Productmentioning
confidence: 99%
“…A small increase in ambient temperature modifies soil water evaporation thus influencing salt transport and distribution in soil. Although the effects of atmospheric conditions on pure water evaporation from porous media are relatively wellunderstood [Smits et al, 2012;Haghighi et al, 2013;Aminzadeh and Or, 2013;Salvucci and Gentine, 2013;Ben Neriah et al, 2014;Vanderborght et al, 2017], their effects on saline water evaporation and the associated salt precipitation patterns are surprisingly not very advanced. Such knowledge will become even more important in the near future with the advent of climate change.…”
Section: Introductionmentioning
confidence: 99%